Adenoma detection rate is enough to assess endoscopist performance: a population-based observational study of FIT-positive colonoscopies - Denis, Bernard; Gendre, Isabelle; Tuzin, Nicolas; Murris, Juliette; Guignard, Anne; Perrin, Philippe; Rahmi, Gabriel (Endoscopy International Open, 2022)
Background and study aims Neoplasia-related indicators, such as adenoma detection rate (ADR), are a priority in the quality improvement process for colonoscopy. Our aim was to assess and compare different detection and characterization indicators in fecal immunochemical test (FIT)-positive colonoscopies, to determine associated factors, and to propose benchmarks.Patients and methods Retrospective analysis of prospectively collected data from all colonoscopies performed between 2015 and 2019 after a positive quantitative FIT in the population-based colorectal cancer screening program conducted in Alsace, part of the French national program. Detection indicators included ADR, mean number of adenomas per colonoscopy, and proximal serrated lesion (SL) detection rate. Characterization indicators included rate of non-neoplastic polyp (NNP) detection.Results Overall, 13,067 FIT-positive colonoscopies were evaluated, performed by 80 community gastroenterologists. The overall ADR was 57.6 %, and a 10 µg/g increase in fecal hemoglobin concentration was significantly associated with higher ADR (odds ratio [95 % confidence interval] = 1.02 [1.02–1.03]). Endoscopists whose ADR was ≥ 55 % were high detectors for all neoplasia, including proximal SLs and number of adenomas. The rate of detection of NNPs was 39.5 % in highest detectors (ADR > 70 %), significantly higher than in lower detectors (21.4 %) (P < 0.001). There was a strong correlation between detection and characterization indicators, e. g. between rates of detection of proximal SLs and NNPs (Pearson = 0.73; P < 0.01).Conclusions A single indicator, ADR, is enough to assess endoscopist performance for both detection and characterization in routine practice provided the minimum target standard is raised and a maximum standard is added: 55 % and 70 % for FIT-positive colonoscopies, respectively.